Impacting Agriculture and Natural Resource Policy: County Commissioners’ Decision-Making Behaviors and Communication Preferences - Kati Lawson; Kevin Kent; Shelli Rampold; Ricky W Telg; Ashley McLeod-Morin (Journal of Applied Communications, 2020)
Elected officials at the local, state, and national levels play key roles in shaping the agriculture and natural resources (ANR) sectors through the development and implementation of ANR policies and regulations. As such, it has become necessary for members of the ANR community to understand the policy formation process and how to communicate effectively with elected officials about ANR policies and issues. However, little research has been conducted at the local level to examine how local elected officials (LEOs) interact with information specific to ANR policies to make decisions. This study was designed to assess the communication and information-seeking preferences and behaviors of LEOs that impact their decisions about ANR issues and policies. Of the sources of communication considered by LEOs when making ANR policy decisions, respondents in this study identified communication from farmers and ranchers as having the highest impact on their decision-making. This finding supports the use of farmers and ranchers as opinion leaders in impacting ANR policies. LEOs in this study also reported they would seek factual information from multiple sources to understand the positive or negative impact of the ANR policy before voting on the ANR issue.
Keywords: agriculture and natural resources; communication; county commissioners; policymaking